An Analysis Performance Reliability Of Air Conditioner Comprecor Motors Based On Power Quality - Julyanto Nehe; Solly Aryza; Zulkarnain Lubis (Sean Institute, 2024)
A Poor power quality, such as voltage fluctuations and harmonic interference, can affect compressor motor performance and life. So this research uses direct measurement and simulation methods to evaluate the influence of various power quality parameters on AC compressor motors. This research aims to analyze the performance reliability of compressor motors in air conditioner (AC) systems based on electrical power quality. and several tests show that harmonic interference and voltage variations significantly affect the efficiency and reliability of the compressor motor. Motors operating under poor power quality conditions exhibit increased operating temperatures, reduced efficiency, and shortened lifespan. The use of harmonic filters and voltage stabilizers has proven effective in improving power quality and, thereby, AC compressor motor performance. This research emphasizes the importance of maintaining power quality to ensure the reliability and efficiency of the compressor motor in the AC system. The implementation of power stabilizer and harmonic filter technology is recommended for industries that use compressor motors extensively, in order to optimize performance and reduce operational costs and made important contributions in the areas of power quality management and preventive maintenance for HVAC (Heating, Ventilation, and Air Conditioning) systems, with a particular focus on compressor motors as a key component in these systems.